Efficiency of Niche Agriculture in Ukraine - Cherevko, Heorhiy; Cherevko, Iryna (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2020)
The deepening of the dualization of Ukraine's agriculture into "large" and "small" producers force the latters to search opportunities for competitive opposition to the firsts by intensive development of niche agriculture. The purpose of the study is to present the efficiency of niche agriculture in Ukraine, describing the main features of this branch and anticipating prospects and barriers to stable development. There are few scientific publications on this topic so far, so their use in the study was quite limited. Materials of specialized scientific conferences and publications of materials of practitioners are more widely used. The research methodology includes general methods (monographic, induction and deduction, analysis and synthesis, scientific generalization and abstraction) as well as economic research methods (comparisons, indexes). The results show, that niche agriculture in Ukraine is especially relevant for small farms, which can increase profitability not because of the number of products, but because of its niche character. Niche agriculture has advantages and disadvantages, so there is no reason to absolutize it as a panacea for all the problems of the small producers. The barriers to develop niche agriculture in Ukraine: the lack of the culture of consumption, of technology and of knowledge of niche products marketing.